ON THE THEORY OF PERSONAL IDENTIFICATION IN THE SYSTEM OF CONTINUOUS PEDAGOGICAL EDUCATION (ANALYSIS OF FOREIGN EXPERIENCE) - A. E. Abylkassymova; S. K. Popey-ool; S. E. Shishov (Scientific Journal of Pedagogy and Economics, 2019)
The article discusses the international experience of research on age identity in the framework of the system of continuous pedagogical education. The authors believe that the existing concepts “identity theory” and “social identification theory” need to add a “differentiated identification theory”, when the individual is a subject of social life and implements a plurality of social roles adopted in society. The article was prepared in the framework of the project “Formation of public consciousness and spiritual and moral culture of students in the system of continuous pedagogical education on the basis of the patriotic idea “Mangilik El”.